Levetiracetam versus phenytoin/fosphenytoin for second-line treatment of children with convulsive status epilepticus: an up-to-date meta-analysis and systematic review of randomized controlled trials - Jin, Linping; Jin, Zhiping; Wang, Zhijiang (Frontiers in Neurology, 2025)
ObjectiveTo compare the efficacy and safety of levetiracetam versus phenytoin/fosphenytoin as second-line treatments in children with convulsive status epilepticus (CSE).MethodsA systematic search identified randomized controlled trials comparing levetiracetam with phenytoin/fosphenytoin to treat CSE in children. Fourteen studies involving 2,197 patients were included in the meta-analysis.ResultsNo significant difference was found between the two treatments regarding seizure cessation (odds ratio (OR): 1.18, 95% confidence interval (CI): 0.94–1.48; p = 0.16) or time to clinical seizure termination (mean difference: −0.10, 95% CI: −0.61 to 0.40; p = 0.69). However, levetiracetam was associated with significantly fewer seizure recurrences (OR: 0.60, 95% CI: 0.43–0.84; p = 0.003) and adverse events (OR: 0.59, 95% CI: 0.37–0.94; p = 0.03) compared with phenytoin/fosphenytoin. No significant differences were observed in the need for mechanical ventilation, intensive care unit admission, or hospital length of stay.ConclusionLevetiracetam is as effective as phenytoin/fosphenytoin to control seizures in children with CSE and is associated with fewer seizure recurrences and adverse events.